Use The Enterprise Resource Planning System To Support The Implementation Of Cost Rationalization and Achieve Effective Management Applied Research In Wasit Textile and Knitting Factory - Maytham Abbas Khudhair Al-Salmawi; Ali Hussein Mahoush (International Forum of Researchers and Lecturers, 2024)
Technology has become one of the important pillars on which organizations that want to succeed in their work depend, as well as those that seek to achieve a leading competitive advantage in their field of work. As they develop, institutions face decisions that require correct information, and the appropriate time for decision-making aims to analyze costs and explain the mechanisms used in the industrial sector in Iraq and the impact of implementing the enterprise resource planning system on the economy. And to display unit costs. Therefore, the complexity of business requires complex information systems that help make good management decisions effectively and efficiently and have a positive impact on financial and non-financial systems.